Rilke-Kommentar zu den "Aufzeichnungen des Malte Laurids Brigge" - Small, William (UNC Studies in the Germanic Languages and Literatures, 1983)
Critics have long regarded Rilke's "Aufzeichnungen des Malte Laurids Brigge" as the first novel in the German language to express in both form and content the artistic direction of the twentieth century. The text's unique form and intricately woven pattern of personal, historical, and literary figures and events have often eluded casual readers and scholars alike. They are nonetheless of great significance to the complex mosaic of themes and motifs which together constitute the artistic unity of the novel. These facts, figures and events correspond for the most part to their respective sources; through Malte's eyes, however, they assume a new perspective that removes them from their historical and personal context and creates a view of the world which is essentially unhistorical and Rilkean in nature. This volume provides the reader with insight into the figures and events referenced in Rilke's novel, as well as an appendix with letters, poems and photographs that provide further historical and literary context.